EVOLVING APPROACHES IN CYBERSECURITY: METRICS AND HUMAN FACTORS (International Seven Journal of Multidisciplinary, 2024)
Recent studies on cybersecurity underscore an increasing recognition of the importance of metrics-driven approaches and adaptable frameworks, particularly for small and medium-sized enterprises (SMEs) that face distinct challenges in a rapidly changing digital landscape. Key developments such as the Cyber Trust Index (CTI) highlight a movement towards methodologies that not only measure security performance quantitatively but also incorporate social and organizational contexts. Additionally, a focus on human factors, including malicious intent, reflects a more nuanced understanding of vulnerabilities within cybersecurity frameworks. The current literature identifies critical gaps in cybersecurity education and workforce development, emphasizing the need for a blend of technical and social skills to foster a culture of responsibility and resilience in organizations. As cybercriminals employ increasingly sophisticated tactics, the integration of advanced technologies, particularly artificial intelligence and cutting-edge cryptographic methods, emerges as a promising avenue for enhancing cybersecurity defenses. In light of the evolving threat landscape, it is essential for organizations and regulators to embrace these innovative practices and frameworks. By adopting effective metrics and remaining adaptable to changing environments, they can bolster their security posture and safeguard critical assets. Ultimately, the establishment of robust metrics and frameworks will facilitate an effective response to cyber threats, paving the way for a more secure future in the digital domain. This strategic shift not only enhances organizational resilience but also contributes to the broader aim of ensuring safety and security in an interconnected world.